Strategic thinkers: a literature review and biographical studies - Witek-Crabb, Anna; Piórkowska, Katarzyna; Lichtarski, Janusz Marek; Wrona, Sylwia; Wilczyński, Maciej Adam (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The main goal of the research was to present fundamental conceptualisations of strategic thinking and strategic thinkers. A thorough literature review led to conceptual conclusions with regards to the understanding of strategic thinking definitions and strategic thinkers’ place in the organisation, as well as characteristics differentiating them from other types of leaders. In the manuscript we also present how strategists vary, forming specific types of strategic thinkers. This led to the identification of a research gap and a goal of strategic thinkers’ typology development. Thanks to biographic studies all strategic thinker types have been illustrated with examples of well-known business leaders.